Cadherins and the pathogenesis of epilepsy. (8th April 2022) - Yang, Ciqing; Shi, Yaping; Li, Xiaoying; Guan, Lihong; Li, Han; Lin, Juntang
Abstract: Epilepsy is a nervous system disease caused by abnormal discharge of brain neurons, which is characterized by recurrent seizures. The factors that induce epilepsy include genetic and environmental factors. Genetic factors are important pathogenic factors of epilepsy, such as epilepsy caused by protocadherin‐19 (PCDH‐19) mutation, which is an X‐linked genetic disease. It is more common in female heterozygotes, which are caused by mutations in the PCDH‐19 gene. Epilepsy caused by environmental factors is mainly caused by brain injury, which is commonly caused by brain tumors, brain surgery, or trauma to the brain. In addition, the pathogenesis of epilepsy is closely related to abnormalities in some signaling pathways. The Wnt/β‐catenin signaling pathway is considered a new target for the treatment of epilepsy. This review summarizes these factors inducing epilepsy and the research hypotheses regarding the pathogenesis of epilepsy. The focus of this review centers on cadherins and the pathogenesis of epilepsy. We analyzed the pathogenesis of epilepsy induced by N‐cadherin and PCDH‐19 in the cadherin family members. Finally, we expect that in the future, new breakthroughs will be made in the study of the pathogenesis and mechanism of epilepsy at the cellular and molecular levels. Key points: The factors that induce epilepsy include genetic and environmental factors. Genetic factors are important pathogenic factors of epilepsy, such as epilepsy caused by protocadherin‐19 (PCDH‐19) mutation, which is an X‐linked genetic disease. Epilepsy caused by environmental factors is mainly caused by brain injury, which is commonly caused by brain tumors, brain surgery, or trauma to the brain.